International practicum: What students gain and are challenged - Bao Kham (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The aim of the study is to explore the effectiveness of the international practicum designated for EFL Vietnamese students who majored in English language teaching and English Language programs. The overseas practicum is the result of the partnership between the University of Foreign Languages and its university partners in Thailand. Within the theoretical framework of Kirkpartrick’s four-level training evaluation model, the study adopted the narrative approach to data collection and analysis, employing in-depth interviews. The study results indicate that the international practicum was effective across the four levels of the model. At the first level, the program effectiveness was manifested in the three aspects, active engagement, high relevance and student satisfaction; at level 2, its effectiveness was exhibited in terms of considerable degrees of knowledge, skills, attitude, confidence and commitment students gained; at level 3, the effective features were demonstrated in substantial extents of application and performance students made; and at the final level, the effectiveness was displayed in significant extents of various impacts the practicum had on the students after the practicum. The findings also show the different challenges students had to face in their oversea placements and also suggestions for improvements from preservice teachers and interns, and their supervisors as well as coordinators. The study findings also suggest noteworthy implications for sustainable practicum outcomes, especially for key stakeholders including students, university faculty and administration.